Association between ophthalmological hemodynamic parameters and the activity of iris neovascularization in patients with neovascular glaucoma (Ukrainian Journal of Ophthalmology, 2026)
Objective. To evaluate the relationship between ophthalmic hemodynamic parameters, particularly the rheographic coefficient (RQ), and the activity of iris neovascularization in neovascular glaucoma (NVG) of different etiologies, as well as to assess the prognostic value of RQ as a functional indicator of ocular microcirculation.Materials and Methods. A total of 224 eyes (224 patients) were examined: 133 with NVG secondary to proliferative diabetic retinopathy (PDR), 91 after ischemic retinal vein occlusion (RVO), and 34 controls with early cataract. Standard ophthalmic examinations included intraocular pressure (IOP), slit-lamp biomicroscopy, and assessment of iris neovascularization by the Weiss scale (Stages I–IV). Rheoophthalmography was used to determine volumetric ocular blood flow (RQ, ‰).Results. Mean RQ values were 3.02 ± 0.41‰ in PDR (hypovolemic type), 3.76 ± 0.39‰ in RVO (hypervolemic type), and 3.34 ± 0.28‰ in controls (normovolemic type). RQ was significantly associated with the degree of iris rubeosis (F(1,229)=66.6; p
Keywords: Neovascular glaucoma; iris rubeosis; ophthalmic hemodynamics; rheoophthalmography; diabetic retinopathy; retinal vein occlusion; microcirculation; retina; iris